Four new genera and five new species of 'Heterocypris' from Western Australia (Crustacea, Ostracoda, Cyprinotinae) - Halse, Stuart A.; Martens, Koen (European Journal of Taxonomy, 2019)
Five new species in four new genera from Western Australia are described. All species have valve characters that are reminiscent of the genus Heterocypris Claus, 1892 and also have similar valve outlines, with highly arched valves. However, all species have a hemipenis morphology that is totally different from the typical form in Heterocypris. In Patcypris gen. nov. (with type species P. outback gen. et sp. nov.), the lateral lobe is large and shaped as a pickaxe, while the medial lobe is divided into two distal lobes. Trilocypris gen. nov. (with type species T. horwitzi gen. et sp. nov.) is characterised by a hemipenis that has three, instead of two, distal lobes. In Bilocypris gen. nov. (with type species B. fortescuensis gen. et sp. nov. and a second species, B. mandoraensis gen. et sp. nov.), the lateral lobe of the hemipenis is spatulate, rather than boot-shaped, and the medial lobe is bilobed. Billcypris gen. nov. (with type species B. davisae gen. et sp. nov.) has a large and sub-rectangular lateral lobe and a pointed medial lobe. We discuss the taxonomic value of the traditional and new morphological characters and speculate that the diversity of this cluster of genera and species may be greater than currently known.